Brand feedback to negative eWOM messages: Effects of stability and controllability of problem causes on brand attitudes and purchase intentions. (May 2021) - Bhandari, Manu; Rodgers, Shelly; Pan, Po-Lin
Highlights: Brand feedback or response to negative eWOM/review can impact visiting consumers. Brand feedback may not work when consumers think problems as stable/likely to endure. Brand feedback may benefit brand- (vs. consumer-) controlled problems more. Abstract: Research has shown negative product reviews or electronic word-of-mouth (eWOM) negatively influence consumers' attitudes and behaviors. However, research has paid less attention to consumers' information processing of negative eWOM in the presence of brands' public response, or brand feedback. Findings from a between-subjects experiment indicate brand feedback can make the biggest impact on visiting consumers when addressing a brand-controlled and short-term problem. This suggests brand feedback cannot replace long-term quality considerations. The study contributes to our understanding of effects of online brand contributions and eWOM messages, and provides managerial suggestions about strategizing posting of brand feedback in an eWOM space.